A novel method for in situ visualization of the growth kinetics, structures and behaviours of gas-phase fabricated metallic alloy nanoparticles. Issue 22 (31st March 2020) - Zhang, Lei; He, Long-Bing; Shi, Lei; Yang, Yu-Feng; Shang, Guan-Lei; Hong, Hua; Sun, Li-Tao
Abstract : In situ visualizing the growth kinetics and behaviours of alloy nanoparticles by a novel EAD method. Abstract : Modulation of gas-phase nanoparticles is unmethodical as there is a lack of information on the growth kinetics and its determinants. Here, we developed a novel in situ evaporation-and-deposition (EAD) method inside a transmission electron microscope which enables direct visualization of the nucleation, growth, coalescence and shape/phase evolution of gas-phase fabricated nanoparticles. Using a Bi49 Pb18 Sn12 In21 alloy as a sample, the critical factors that determine the feasibility of this EAD method are revealed. By direct observation, it is unambiguously evidenced that pristine nanoparticles with ultra-clean surfaces are extremely energetic during growth. Coalescence between EAD-fabricated nanoparticles takes place in a manner beyond conventional understanding acquired by postmortem analyses. Moreover, the EAD-fabricated diverse nanoparticles show distinct size distributions and sandwich-type or Janus-type phase segregations. These features offer an effective tool to identify atomic surface steps of thin films and can provide an ideal case for exploring the phase diagrams of nanoalloys in the future.